nalisis Pengakuan Pendapatan dan Penyaluran Zakat Infak Sedekah Untuk Pelaporan Keuangan Berdasarkan PSAK 109 Pada Yayasan Amanah Takaful - Yohanes Sugiyanta; R Taufik Hidayat (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
This research was conducted at Yayasan Amanah Takaful. This study aims to determine how revenue recognition, recognition of zakat distribution, and presentation of financial statements at the Amanah Takaful Foundation. The research method used in this research is the data collection method by conducting interviews and observations as well as conducting literature studies related to revenue recognition, recognition of distribution and presentation of financial statements at the Amanah Takaful Foundation. The results showed that the Foundation has fully implemented the provisions regarding revenue recognition of Zakat, Infaq and Sadaqah Funds in accordance with PSAK No. 109 where it should be done on the financial statements of the Amanah Takaful Foundation. The foundation has implemented PSAK No. 109 by recording directly when receiving ZIS funds or assets / goods. In addition, the Amanah Takaful Foundation has implemented the provisions regarding the distribution of zakat, infaq and alms in accordance with PSAK No. 109 The amount of distribution of zakat funds in 2022 amounted to Rp. 2,416,780,508 and the distribution of bound infaq in 2022 amounted to Rp. 85,358,764 and the distribution of unbound infaq amounted to Rp. 3,353,283,982 so that the total distribution of infaq 2022 amounted to Rp. 3,353,283,982. Revenue recognition and distribution of ZIS in accordance with PSAK No. 109 greatly affect financial reporting. However, the foundation has not presented financial reporting as stipulated in accordance with PSAK No. 109.